Numerical modelling of wave-induced pore pressure around a buried pipeline:WSPI-3D model - Shabani, Behnam; Jeng, Dong-Sheng; Ye, Jianhong; Guo, Yakun (American Society of Mechanical Engineers, 2010)
In this paper a three-dimensional numerical model is developed to analyze the ocean wave-induced seabed response. The pipeline is assumed to be rigid and anchored within a trench. Quasi-static soil consolidation equations are solved with the aid of the proposed Finite Element (FE) model within COMSOL Multiphysics. The influence of wave obliquity on seabed responses, the pore pressure and soil stresses, are studied. A comprehensive tests of FE meshes is performed to determine appropriate meshes for numerical calculations. The present model is verified with the previous analytical solutions without a pipeline and two-dimensional experimental data with a pipeline. Numerical results suggest that the effect of wave obliquity on soil responses can be explained through the following two mechanisms: (i) geometry-based three-dimensional influences, and (ii) the formation of inversion nodes. However the influences of wave obliquity on the wave-induced pore pressure are insignificant.